The Influence of Tax Planning, Deferred Tax Expenses, and Deferred Tax Assets on Profit Management in Energy Sector Companies Listed on the Indonesian Stock Exchange - Dinda Pratiwi; , Fuad Ramdhan Ryanto (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study seeks to assess how tax planning, deferred tax expenses, and deferred tax assets impact profit management within energy sector firms listed on the Indonesian Stock Exchange. Employing an associative research approach, data was collected through documentation studies utilizing secondary data. From the subsequent analysis and discussions, the following conclusions emerge: 1) The multiple linear regression equation, representing the influence of tax planning, deferred tax expenses, and deferred tax assets on earnings management, is as follows: Y= 11.615 + (-2.18X?) + 0.485X2 + 0.252X3 + e. 2) With a correlation coefficient (r) of 0.341, it suggests a weak relationship between Tax Planning variables, Deferred Tax Expenses, Deferred Tax Assets, and the Profit Management variable. 3) The coefficient of determination (R2) at 0.117 indicates that Tax Planning, Deferred Tax Expenses, and Deferred Tax Assets collectively influence earnings management by 11.7%, while the remaining 88.3% of variance is attributed to unexplored variables. 4) Results from the F statistical test exhibit a significance value (Sig.) of 0.041 < 0.05, indicating a significant joint influence of Tax Planning, Deferred Tax Expenses, and Deferred Tax Assets on Profit Management. 5) Through the t test (partial), it is found that Tax Planning does not exert a significant influence on Profit Management. Conversely, Deferred Tax Expenses significantly impact Profit Management, whereas Deferred Tax Assets do not significantly influence Profit Management.